Cement-based material for fixing neutron activation material and application of cement-based material

By using admixtures in cement-based materials and boric acid to work together to generate hydration products with high crystalline water content, the problem of cement-based materials strongly inhibiting hydration reaction in high boron solution is solved, and the high-middle shielding and mechanical properties of cement cured bodies are improved.

CN119841607APending Publication Date: 2025-04-18WUHAN UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411916605.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

When existing cement-based materials are mixed with high boron solution, they strongly inhibit the hydration reaction of cement particles, greatly reducing the strength of the cement cured body, and unable to meet the engineering requirements of neutron shielding capabilities.

Method used

By adding admixtures to the cement-based material and working together with boric acid, the presence status of borate is adjusted, and induced to generate hydrated products with high crystalline water content, such as boron cured ettringite, calcium borate tetrahydrate, and calcium metaborate, to improve the uniform distribution of boron and hydrogen elements, thereby enhancing the neutron absorption cross-section.

Benefits of technology

It effectively improves the neutron absorption cross-section and mechanical properties of cement cured bodies, enhances the shielding ability of neutron rays, and meets the performance indicators required by engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a cement-based material for immobilizing a neutron activation material, and belongs to the technical field of immobilizing materials for treating radioactive nuclear waste, the cement-based material comprises 5-10 parts of boron nitride, 80-120 parts of a gel material, 50-80 parts of a boric acid solution, 8-20 parts of an additive, 0.2-3 parts of a nucleating agent, 0.5-2 parts of a water reducing agent and 0.5-3 parts of a foaming agent, the concentration of the boric acid solution is 3-6 mol / L, the additive comprises sodium hydroxide and sodium aluminate, and the foaming agent comprises sodium hydroxide and sodium aluminate. The nucleating agent comprises one or more of synthetic hydrated calcium silicate gel, layered double hydroxides and a carbon nanomaterial. The admixture and boric acid are jointly added into the gel material, sodium hydroxide in the admixture can adjust the occurrence state of borate, sodium aluminate can promote formation of hydration products such as ettringite, and therefore the content of boron and hydrogen in a cement solidified body is effectively increased, and the shielding capacity of the cement solidified body for neutron rays is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fixing materials for treating radioactive nuclear waste, and in particular to a cement-based material for fixing neutron activation materials and application thereof. Background Art

[0002] Neutrons are neutral particles with strong penetrating power. In the process of colliding with atomic nuclei, they transfer energy to atomic nuclei to produce secondary charged particles, thereby causing indirect ionizing radiation. For neutron radiation protection, it is necessary to first slow down the neutrons, and then use elements with a large neutron absorption cross section to absorb the slowed down neutrons. At present, with the rapid development of nuclear technology and application research, in the field of radiation protection, people are increasingly studying the neutron shielding properties of typical shielding materials. When shielding neutrons, hydrogen-rich or low atomic number materials are usually used to slow down the neutrons, and then materials with a large neutron absorption cross section are used to absorb the neutrons. At present, the former usually uses some crystals containing a large amount of crystal water, and the crystals need to maintain the stability of crystal water in a long-term high temperature environment and a long-term high radiation environment; the latter usually uses some nuclides with a large neutron absorption cross section, among which the boron element in the nuclides with a large neutron absorption cross section is abundant and cheap. The proportion of crystal water and the amount of boron in shielding cement concrete will affect the ability of shielding concrete to shield neutron rays. Although the concrete currently used for nuclear energy protection is rich in crystal water, it lacks elements with strong neutron absorption ability, so its ability to resist neutron rays needs to be strengthened.

[0003] The method of increasing the boron content in cement paste is still in the research and exploration stage. Boric acid is a strong retarder for cement. When existing cement-based materials are mixed with high-boron solution, they have low boron content and the paste strength cannot meet the requirements of GB14569.1-2011 "Performance Requirements for Solidified Low and Medium Level Radioactive Waste-Concrete". The key reason is that the high-boron solution contains more than 21.2% boric acid by mass, and the high-concentration boric acid solution can form a dense coating of calcium borate or borax on the surface of cement particles during cement hydration, blocking the contact between water and cement particles, strongly inhibiting the further hydration reaction of cement particles, and greatly reducing the strength of concrete, so that it cannot meet the various properties of concrete required by GB14569.1-2011 and cannot meet engineering requirements. Summary of the invention

[0004] In view of the technical problems existing in the background technology, the present application provides a cement-based material for fixing neutron activation material and its use, aiming to solve the technical problem that the cement-based material in the neutron shielding cement solid body strongly inhibits the hydration reaction of cement particles when mixed with a high boron solution, thereby significantly reducing the strength of the cement solid body.

[0005] In the first aspect, an embodiment of the present application provides a cement-based material for fixing a neutron activation material, which comprises, by mass, 5 to 10 parts of boron nitride, 80 to 120 parts of a gel material, 50 to 80 parts of a boric acid solution, 8 to 20 parts of an admixture, 0.2 to 3 parts of a nucleating agent, 0.5 to 2 parts of a water reducing agent, and 0.5 to 3 parts of a foaming agent, wherein the concentration of the boric acid solution is 3 to 6 mol / L, the admixture comprises sodium hydroxide and sodium aluminate, and the nucleating agent comprises one or more of a synthetic hydrated calcium silicate gel, a layered double hydroxide, and a nanocarbon material.

[0006] In some embodiments, the additive also includes sodium carbonate, and the mass ratio of sodium hydroxide, sodium aluminate and sodium carbonate is (0.4~0.7): (0.2~0.7): (0~0.5).

[0007] In some embodiments, the mass ratio of synthetic hydrated calcium silicate gel, layered double hydroxide, and nanocarbon material in the nucleating agent is (0.3~1):(0~0.7):(0~0.7), and the nanocarbon material includes one or two of graphene oxide and carbon nanotubes.

[0008] In some embodiments, the boron nitride particle size is 0.1-0.5 mm.

[0009] In some embodiments, the water reducer is a high-efficiency naphthalene-based water reducer or a high-efficiency polycarboxylic acid-based water reducer.

[0010] In some embodiments, the foaming agent is 30 wt % hydrogen peroxide solution or aluminum powder.

[0011] In some embodiments, the gel material includes cement, fly ash, mineral powder and silica ash in a mass ratio of (70~100):(0~15):(0~15):(0~15); the cement is PO 52.5 model cement; the fly ash is first-class fly ash; the mineral powder model is S95; the silica ash is first-class silica ash, and the purity of silica ash SiO2 is ≥90%.

[0012] In a second aspect, an embodiment of the present application provides a use of a cement-based material for fixing a neutron activation material, wherein the cement-based material is used to fix the neutron activation material.

[0013] In some embodiments, the neutron activation material includes one or more of nuclear reactor blanket structural materials, nuclear reactor lining materials, plasma-facing materials, and reactor structural materials; the reactor structural materials include one or more of austenitic stainless steel, martensitic steel, vanadium alloy, SiCf / SiC composite material, oxide dispersion strengthened steel, carbon material, beryllium material, tungsten material, amorphous material, and high entropy alloy.

[0014] In some embodiments, the cement-based material fixes the neutron-activated material and comprises the following steps: after mixing and stirring boron nitride, gel material, nucleation agent, water reducer and foaming agent, add boric acid solution and admixture and stir, then add foaming agent and mix evenly to obtain cement-based slurry, use cement-based slurry for grouting, coat the neutron-activated material to form a cement solid body, and achieve its fixation; the volume of cement-based material in the cement solid body is not less than 40%.

[0015] Different from the existing technical solutions, the beneficial effects of this application include: 1. In the present application, an admixture and boric acid are added to the gel material together. The sodium hydroxide in the admixture can adjust the occurrence state of borate by adjusting the complex and large borate at low pH to tetrahydroxyborate at high pH. At the same time, the presence of sodium aluminate and sodium carbonate can also promote the formation of hydration products such as calcium sulfonate and further increase the pH value, so that in the cement-based hydration reaction, boron-solidified calcium sulfonate, calcium borate tetrahydrate, calcium metaborate and other hydration products with high crystal water content are induced to form, so that boron and hydrogen elements are evenly distributed inside the slurry, thereby effectively increasing the boron and hydrogen content in the cement solid body, increasing the neutron absorption cross-section of the cement solid body, and enhancing the shielding ability of the matrix to neutron rays.

[0016] 2. The boric acid solution modified by the admixture is strongly alkaline, and the mechanical properties of the cement solidified body are improved through the alkali excitation mechanism. The sodium aluminate and sodium carbonate in the admixture are dissolved to form the precursor of the hydration product, so that the free borate is solidified to form boron-solidified ettringite, calcium borate tetrahydrate, calcium metaborate and other high-boron-containing phases, so it will not hinder the hydration reaction of the cement. The strong alkaline modified boric acid solution and the generated boron-solidified ettringite and other boron-containing phases work together to make the boron-solidified ettringite, calcium borate tetrahydrate, and calcium metaborate more stable, while achieving a more uniform distribution of boron and hydrogen elements in the neutron shielding cement solidified body, and at the same time achieving a synchronous improvement in the fast neutron slowing down and thermal neutron absorption effects.

[0017] 3. Nucleating agents can promote the rapid formation of boron-containing minerals, while promoting the hydration process of cement paste, improving the strength and durability of cement paste, and reducing the porosity of the solidified body. The synergistic effect of nucleating agents and admixtures can provide a cement solidified body with a hydrogen content of 2-4% of the paste mass and a boron content of 2-3% of the paste mass, which has high strength, strong neutron shielding ability, good thermal stability, good construction and workability, and easy access to raw materials, which is suitable for wide promotion and application.

[0018] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. DETAILED DESCRIPTION

[0019] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the description and claims of this application and any variations thereof are intended to cover non-exclusive inclusions.

[0021] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0022] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0023] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0024] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0025] The method of increasing the boron content in cement paste is still in the research and exploration stage. Boric acid is a strong retarder for cement. When the existing cement-based materials are mixed with high-boron solution, they have low boron content and the slurry strength cannot meet the requirements of GB14569.1-2011 "Performance Requirements for Low and Medium Level Radioactive Waste Solidification - Cement Solidification". The key reason is that the high-boron solution contains more than 21.2% boric acid by mass, and the high-concentration boric acid solution can form a dense coating layer of calcium borate or borax on the surface of cement particles during cement hydration, blocking the contact between water and cement particles, strongly inhibiting the further hydration reaction of cement particles, and greatly reducing the strength of the cement solidification body, so that it cannot meet the various properties of the cement solidification body required by GB14569.1-2011 and cannot meet the engineering requirements.

[0026] In order to solve the technical problem that when cement-based materials in neutron-shielding cement solids are mixed with high-boron solutions, the hydration reaction of cement particles is strongly inhibited, thereby greatly reducing the strength of the cement solids. The present application provides a cement-based material for fixing neutron-activated materials and its use, wherein an admixture is added to a gel material together with boric acid, and the admixture can adjust the occurrence state of borate ions, so that in the hydration reaction mainly based on cement, boron-solidified calcium sulfoxide, calcium borate tetrahydrate, calcium metaborate and other hydration products with high crystalline water content are induced to form, so that boron and hydrogen elements are evenly distributed inside the slurry, thereby effectively increasing the content of boron and hydrogen elements in the cement solid, increasing the neutron absorption cross-section of the cement solid, and enhancing the shielding ability of the matrix against neutron rays.

[0027] In the first aspect, an embodiment of the present application provides a cement-based material for fixing a neutron activation material, which comprises, by mass, 5 to 10 parts of boron nitride, 80 to 120 parts of a gel material, 50 to 80 parts of a boric acid solution, 8 to 20 parts of an admixture, 0.2 to 3 parts of a nucleating agent, 0.5 to 2 parts of a water reducing agent, and 0.5 to 3 parts of a foaming agent, wherein the concentration of the boric acid solution is 3 to 6 mol / L, the admixture comprises sodium hydroxide and sodium aluminate, and the nucleating agent comprises one or more of a synthetic hydrated calcium silicate gel, a layered double hydroxide, and a nanocarbon material.

[0028] In the technical scheme of the embodiment of the present application, compared with the addition of soluble borates alone, a layer of amorphous boraxite will be formed on the surface of cement particles, resulting in cement particles being unable to continue hydration for a long time, causing cement paste to have no strength development. In this application, sodium hydroxide, sodium aluminate and sodium carbonate are combined, and the sodium hydroxide in the admixture can adjust the state of occurrence of borate, by adjusting the complex and large borate at low pH to tetrahydroxyborate at high pH; At the same time, the presence of sodium aluminate and sodium carbonate can also promote the formation of hydration products such as calcium sulfonate and further increase the pH value, so that in the hydration reaction mainly based on cement, it induces the formation of hydration products with high crystal water content such as boron solidified calcium sulfonate, calcium tetrahydrate borate, and calcium metaborate, so that boron and hydrogen elements are evenly distributed inside the slurry, thereby effectively increasing the content of boron and hydrogen elements in concrete, increasing the neutron absorption cross section of cement solidified body, and enhancing the shielding ability of the matrix to neutron rays. If only sodium hydroxide is added as an admixture, the prepared cement solidified body is difficult to coagulate.

[0029] The boric acid solution modified by admixtures is strongly alkaline, and improves the mechanical properties of concrete through the alkali excitation mechanism, and the free borate is solidified into high-boron-containing phases such as boron-solidified ettringite, calcium borate tetrahydrate, and calcium metaborate, so it will not hinder the hydration reaction of cement. The strongly alkaline modified boric acid solution and the generated boron-solidified ettringite and other boron-containing phases work together to make boron-solidified ettringite, calcium borate tetrahydrate, and calcium metaborate more stable, while achieving a more uniform distribution of boron and hydrogen elements in neutron shielding concrete, and simultaneously improving the fast neutron slowing and thermal neutron absorption effects.

[0030] In some embodiments, the additive also includes sodium carbonate, and the mass ratio of sodium hydroxide, sodium aluminate and sodium carbonate is (0.4~0.7): (0.2~0.7): (0~0.5).

[0031] In the technical solution of the embodiment of the present application, if the amount of admixture added is too high, the strength of the cement solidification body will be reduced and alkali efflux will lead to reduced durability of the matrix. If the proportion is too low, the setting time will be too long, affecting the strength development and thus the durability of the matrix.

[0032] In some embodiments, the mass ratio of synthetic hydrated calcium silicate gel, layered double hydroxide, and nanocarbon material in the nucleating agent is (0.3~1):(0~0.7):(0~0.7), and the nanocarbon material includes one or two of graphene oxide and carbon nanotubes.

[0033] In the technical solution of the embodiment of the present application, the nucleating agent can promote the rapid formation of boron-containing minerals, while promoting the hydration process of the cement slurry, improving the strength and durability of the cement slurry, and reducing the porosity of the solidified body.

[0034] In some embodiments, the boron nitride particle size is 0.1-0.5 mm.

[0035] In the technical solution of the embodiment of the present application, the boron carbide particles as fine aggregate can effectively increase the content of boron element in the cement solidification body and improve the shielding ability of the cement paste against neutron rays.

[0036] In some embodiments, the water reducer is a high-efficiency naphthalene-based water reducer or a high-efficiency polycarboxylic acid-based water reducer.

[0037] In the technical solution of the embodiment of the present application, by adding a high-efficiency naphthalene-based water-reducing agent or a high-efficiency polycarboxylic acid water-reducing agent, the cement slurry has better workability and fluidity, which is beneficial to engineering applications.

[0038] In some embodiments, the foaming agent is 30 wt % hydrogen peroxide solution or aluminum powder.

[0039] In the technical solution of the embodiment of the present application, the foaming agent can produce a large number of bubbles inside the slurry, thereby improving the thermal shock resistance of the slurry, reserving space for the gas generated by neutron radiation, and improving the durability of the slurry.

[0040] In some embodiments, the gel material includes cement, fly ash, mineral powder and silica ash in a mass ratio of (70~100):(0~15):(0~15):(0~15); the cement is PO 52.5 model cement; the fly ash is first-class fly ash; the mineral powder model is S95; the silica ash is first-class silica ash, and the purity of silica ash SiO2 is ≥90%.

[0041] In the technical solution of the embodiment of the present application, the addition of mineral powder and fly ash to cement can effectively reduce the early hydration heat of cement solidification and reduce the risk of cracking of cement solidification in engineering applications. At the same time, the addition of mineral powder and fly ash can enhance the high temperature resistance of cement paste and increase the service life of cement solidification under high temperature conditions.

[0042] In a second aspect, an embodiment of the present application provides a use of a cement-based material for fixing a neutron activation material, wherein the cement-based material is used to fix the neutron activation material.

[0043] In some embodiments, the neutron activation material includes one or more of nuclear reactor blanket structural materials, nuclear reactor lining materials, plasma-facing materials, and reactor structural materials; the reactor structural materials include one or more of austenitic stainless steel, martensitic steel, vanadium alloy, SiCf / SiC composite material, oxide dispersion strengthened steel, carbon material, beryllium material, tungsten material, amorphous material, and high entropy alloy.

[0044] In some embodiments, the cement-based material fixes the neutron-activated material and comprises the following steps: after mixing and stirring boron nitride, gel material, nucleation agent, water reducer and foaming agent, add boric acid solution and admixture and stir, then add foaming agent and mix evenly to obtain cement-based slurry, use cement-based slurry for grouting, coat the neutron-activated material to form a cement solid body, and achieve its fixation; the volume of cement-based material in the cement solid body is not less than 40%.

[0045] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0046] 1. Preparation method Example 1 A method for preparing a cement-based slurry for fixing neutron activation materials is as follows: 5 kg of boron carbide, 90 kg of PO 52.5 cement, 20 kg of fly ash, 10 kg of silica fume, 0.3 kg of synthetic hydrated calcium silicate gel, and 0.6 kg of high-efficiency polycarboxylate water reducer were mixed and stirred for 3 minutes, and then 50 kg of boric acid solution with a concentration of 5 mol / L was added, 4.8 kg of sodium hydroxide, 2 kg of sodium aluminate, and 1.2 kg of sodium carbonate were stirred and mixed for 2 minutes, and then 1.1 kg of hydrogen peroxide was added and stirred for 3 minutes to prepare a cement-based slurry.

[0047] Example 2 A method for preparing a cement-based slurry for fixing neutron activation materials is as follows: 7kg of boron carbide, 70kg of PO 52.5 cement, 10kg of fly ash, 10kg of mineral powder, 10kg of silica fume, 0.3kg of synthetic hydrated calcium silicate gel, 0.7kg of layered double hydroxide, and 1.0kg of high-efficiency polycarboxylate water reducer were mixed and stirred for 3 minutes, and then 65kg of boric acid solution with a concentration of 5mol / L was added, 7kg of sodium hydroxide, 3kg of sodium aluminate, and 1kg of sodium carbonate were stirred and mixed for 2 minutes, and then 1.1kg of hydrogen peroxide and 1.4kg of aluminum powder were added and stirred for 3 minutes to prepare a cement-based slurry.

[0048] Example 3 A method for preparing a cement-based slurry for fixing neutron activation materials is as follows: 8.5 kg of boron carbide, 100 kg of PO 52.5 cement, 5 kg of fly ash, 7 kg of mineral powder, 0.6 kg of synthetic hydrated calcium silicate gel, 1.4 kg of nano-graphene oxide, and 1.7 kg of high-efficiency polycarboxylate water reducer were mixed and stirred for 3 minutes, and then 71 kg of boric acid solution with a concentration of 5 mol / L was added, 5.2 kg of sodium hydroxide and 7.8 kg of sodium aluminate were stirred and mixed for 2 minutes, and then 1.1 kg of hydrogen peroxide was added and stirred for 3 minutes to prepare a cement-based slurry.

[0049] Example 4 A method for preparing a cement-based slurry for fixing neutron activation materials is as follows: 8.5 kg of boron carbide, 100 kg of PO 52.5 cement, 10 kg of mineral powder, 10 kg of silica fume, 0.1 kg of synthetic hydrated calcium silicate gel, 0.1 kg of layered double hydroxide, 0.1 kg of carbon nanotubes, and 1.7 kg of high-efficiency naphthalene-based water reducer were mixed and stirred for 3 minutes, and then 75 kg of boric acid solution with a concentration of 5 mol / L was added, 8 kg of sodium hydroxide, 5 kg of sodium aluminate, and 3 kg of sodium carbonate were stirred and mixed for 2 minutes, and then 2.1 kg of aluminum powder was added and stirred for 3 minutes to prepare a cement-based slurry.

[0050] Example 5 A method for preparing a cement-based slurry for fixing neutron activation materials is as follows: 10 kg of boron carbide, 105 kg of PO 52.5 cement, 0.3 kg of synthetic hydrated calcium silicate gel, 0.2 kg of layered double hydroxide, 0.1 kg of carbon nanotubes, and 2.0 kg of high-efficiency polycarboxylic acid water reducer were mixed and stirred for 3 minutes, and then 80 kg of boric acid solution with a concentration of 5 mol / L was added, 10 kg of sodium hydroxide, 5 kg of sodium aluminate, and 5 kg of sodium carbonate were stirred and mixed for 2 minutes, and then 3.0 kg of hydrogen peroxide was added and stirred for 3 minutes to prepare a cement-based slurry.

[0051] Comparative Example 1 Comparative Example 1 is based on Example 3, except that the boric acid solution and the additive are removed and tap water of equal mass is used instead. The other components are the same as the preparation method.

[0052] Comparative Example 2 Comparative Example 2 is based on Example 3 except for the addition of the additive, and the other components are the same as the preparation method.

[0053] Comparative Example 3 Comparative Example 3 is based on Example 3 except that the crystal nucleating agent is removed, and the other components are the same as the preparation method.

[0054] 2. Test Method 1. Compressive strength test method The compressive strength of the samples was tested using the methods in national standards GB / T 17671-2021 and GB 14569.1-2011. The compressive strength test was conducted after the samples were cured to the standard age.

[0055] 2. Test method for hydrogen content of solidified body The hydrogen content of the solidified body is tested by low-field nuclear magnetic resonance. After the sample is cured to the required age, the sample is tested by low-field nuclear magnetic resonance, and the hydrogen content is estimated by the water content.

[0056] 3. Test method for boron content in solidified body The hydrogen content of the solidified body is tested by inductively coupled plasma (ICP). The boron concentration of the cement paste is tested by ICP after it is dissolved by strong acid to estimate the boron content.

[0057] 4. Test method for strength loss rate after freeze-thaw cycles According to the method in the national standard GB 14569.1-2011, the samples were subjected to freeze-thaw cycle test after 28 days of curing, and the strength test was carried out after five cycles. The strength loss rate after freeze-thaw cycle = 100% × (strength before freeze-thaw cycle - strength after freeze-thaw cycle) / strength before freeze-thaw cycle.

[0058] 5. Strength loss rate after anti-immersion According to the method in the national standard GB 14569.1-2011, the samples were subjected to immersion test after 28 days of curing, and strength test was conducted after 90 days of immersion. The strength loss rate after immersion = 100% × (strength before immersion - strength after immersion) / strength before immersion.

[0059] 6. Strength loss rate after γ-irradiation According to the method in the national standard GB 14569.1-2011, the samples were subjected to γ ​​irradiation test after 28 days of curing. The irradiation dose was about 1 kGy / h. The strength test was carried out after the total irradiation reached 1 MGy. The strength loss rate after γ irradiation = 100% × (strength before irradiation - strength after irradiation) / strength before irradiation.

[0060] 7. Cement solidified body radiation attenuation coefficient The linear absorption coefficient (μ) of the samples was tested according to the standard test method of the 719th Institute of China Shipbuilding Heavy Industry "Test Method for Shielding Performance of Ionizing Radiation Protection Materials" (Q / 719J131_2018).

[0061] Ix=I0e-μx Among them, μ is the linear absorption coefficient; I0 ​​is the intensity of the incident ray; Ix is the intensity after incidence; x is the thickness of the sample.

[0062] III. Analysis of test results of various embodiments and comparative examples (1) The cement-based slurries prepared in the above-mentioned embodiments and comparative examples were cured for 28 days to obtain cement solidified bodies, and the compressive properties of the cement solidified bodies cured at 400°C for 28 days were tested. The hydrogen content and boron content of the solidified bodies were then tested. The test results are shown in Table 1.

[0063] Table 1 Test data of compressive properties of cement solidified body, hydrogen content and boron content of solidified body

[0064] As can be seen from Table 1, the 28-day compressive strength of Examples 1 to 5 at room temperature and high temperature is higher than that of Comparative Examples 1 to 3, and the compressive strength increases with the increase in the amount of boric acid solution, admixture and crystal nucleating agent. This is because the combined effect of the simultaneous addition of boric acid solution, admixture and crystal nucleating agent can improve the mechanical properties of cement solidified body. Comparative Example 2 did not condense at room temperature for 28 days, and the compressive strength was 0, because the addition of boric acid solution alone caused the cement solidified body to be unable to condense due to the strong hindrance of boron element to cement hydration. Therefore, the subsequent high temperature strength and ray attenuation coefficient of Comparative Example 2 were not tested. The 28-day compressive strength of Comparative Example 3 at room temperature and high temperature was slightly higher than that of Comparative Example 1 but lower than that of Example 3, because the addition of crystal nucleating agent can improve the hydration degree of slurry, so that the mechanical properties of cement solidified body are improved, so the lack of crystal nucleating agent is lower than the combined effect of boric acid, special admixture and crystal nucleating agent in Example 3. The high-temperature compressive strength of each embodiment and comparative example is improved compared with that at room temperature because the addition of fly ash and mineral powder causes secondary hydration of the slurry under high temperature conditions, promoting strength growth. The above comparison shows that the improvement of the mechanical properties at room temperature and high temperature of the present invention is due to the combined effect of the boric acid solution, the admixture and the crystal nucleating agent, rather than the simple addition of the two separate effects.

[0065] In the comparison of hydrogen content, the hydrogen content of Examples 1 to 5 is much greater than that of Comparative Examples 1 to 3, indicating that the combined introduction of boric acid solution, admixture and nucleating agent can increase the hydrogen content in the cement solidified body. Comparative Example 3 is greater than Comparative Example 2 and Comparative Example 1, indicating that the boric acid solution, admixture and nucleating agent can all increase the hydrogen content in the cement solidified body, and the boric acid solution introduces more hydrogen elements, but the sum of the hydrogen content increase achieved by the three acting in pairs cannot achieve the effect of the combined action of the three, indicating that the combined action of the two produces a new effect.

[0066] In the comparison of boron content, the boron content of Examples 1 to 5 and Comparative Examples 1 to 3 is related to the amount of boron carbide and boric acid solution added to the cement solidified body, because boron carbide or boron compounds will not volatilize during room temperature curing or high temperature treatment. The boron content of Examples 2 to 5 is greater than that of Comparative Examples 1 to 3, indicating that the introduction of boric acid solution in the present application can increase the boron content in the cement solidified body.

[0067] (2) The cement solidified bodies of the cement-based slurries prepared in the above-mentioned embodiments and comparative examples after curing for 28 days were subjected to freeze-thaw cycle resistance test, immersion resistance test and gamma irradiation resistance test, and the strengths before and after the completion of different durability tests were compared. The test results are shown in Table 2 below.

[0068] Table 2 Durability test results of cement solidified body

[0069] As can be seen from Table 2, the durability of Examples 1 to 5 is better than that of Comparative Examples 1 to 3, and has better resistance to gamma ray irradiation, indicating that the combined effect of adding boric acid solution, admixture and nucleating agent can improve the durability of cement solidified body, so that it still has good neutron shielding performance under complex environment. In Comparative Examples 2 to 3, no admixture or nucleating agent was added, which reduced the high temperature resistance of cement solidified body. The above results show that the new effect produced by the combined effect of boric acid solution, admixture and nucleating agent in the present invention greatly improves the durability of cement solidified body.

[0070] (3) The shielding performance of the cement solidified bodies of the cement-based slurries prepared in the above-mentioned embodiments and comparative examples after curing for 28 days was tested, and the radiation absorption coefficients of the cement solidified bodies were obtained as shown in Table 3 below.

[0071] Table 3 Cement solidified body radiation absorption coefficient (cm -1 )

[0072] It can be seen from Table 3 that the gamma-ray and neutron-ray shielding capabilities of Examples 1 to 5 are significantly better than those of Comparative Examples 1 to 3, and are enhanced with the increase in the amount of boric acid solution, admixture and nucleating agent, indicating that the improvement in the shielding capability of the cement solid body against gamma-rays and neutron rays comes from the new effect produced by the combined application of boric acid, admixture and nucleating agent.

[0073] In summary, the present application provides a neutron activated material cement solidified body with high performance, excellent high temperature resistance and excellent shielding performance, which is suitable for wide promotion and application.

[0074] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A cement-based material for fixing neutron activation material, characterized in that: Calculated by mass, the invention comprises 5-10 parts of boron nitride, 80-120 parts of gel material, 50-80 parts of boric acid solution, 8-20 parts of additive, 0.2-3 parts of crystal nucleating agent, 0.5-2 parts of water reducing agent and 0.5-3 parts of foaming agent, the concentration of the boric acid solution is 3-6 mol / L, the additive comprises sodium hydroxide and sodium aluminate, and the crystal nucleating agent comprises one or more of synthetic hydrated calcium silicate gel, layered double hydroxide and nano-carbon material.

2. The cement-based material for fixing neutron activation material according to claim 1, characterized in that: The additive also includes sodium carbonate, and the mass ratio of the sodium hydroxide, sodium aluminate and sodium carbonate is (0.4-0.7): (0.2-0.7): (0-0.5).

3. The cement-based material for fixing neutron activation material according to claim 1, characterized in that: The mass ratio of the synthetic hydrated calcium silicate gel, the layered double hydroxide and the nano-carbon material in the nucleating agent is (0.3-1): (0-0.7): (0-0.7), and the nano-carbon material includes one or two of graphene oxide and carbon nanotubes.

4. The cement-based material for fixing neutron activation material according to claim 1, characterized in that: The boron nitride particle size is 0.1-0.5 mm.

5. The cement-based material for fixing neutron activation material according to claim 1, characterized in that: The water reducer is a high-efficiency naphthalene-based water reducer or a high-efficiency polycarboxylic acid-based water reducer.

6. The cement-based material for fixing neutron activation material according to claim 1, characterized in that: The foaming agent is 30wt% hydrogen peroxide solution or aluminum powder.

7. The cement-based material for fixing neutron activation material according to claim 1, characterized in that: The gel material includes cement, fly ash, mineral powder and silica ash, and the mass ratio is (70~100):(0~15):(0~15):(0~15); the cement is PO 52.5 model cement; the fly ash is first-class fly ash; the mineral powder model is S95; the silica ash is first-class silica ash, and the SiO2 purity of the silica ash is ≥90%.

8. The use of a cement-based material for fixing a neutron activation material according to claim 1, characterized in that: The neutron activation material is fixedly disposed using the cement-based material as described in any one of claims 1 to 7.

9. The use of a cement-based material for fixing a neutron activation material according to claim 8, characterized in that: The neutron activation material includes one or more of nuclear reactor blanket structural materials, nuclear reactor lining materials, plasma-facing materials, and reactor structural materials; the reactor structural materials include one or more of austenitic stainless steel, martensitic steel, vanadium alloy, SiCf / SiC composite material, oxide dispersion strengthened steel, carbon material, beryllium material, tungsten material, amorphous material, and high entropy alloy.

10. The use of a cement-based material for fixing a neutron activation material according to claim 8, characterized in that: The cement-based material fixes the neutron activation material and comprises the following steps: mixing and stirring boron nitride, gel material, nucleation agent, water reducer and foaming agent, adding boric acid solution and admixture and stirring and mixing, then adding foaming agent and mixing evenly to obtain cement-based slurry, grouting with cement-based slurry, coating the neutron activation material to form a cement solidified body, and achieving the fixation of the neutron activation material; the volume of cement-based material in the cement solidified body is not less than 40%.

Citation Information

Cited By

  • Quick-setting and quick-hardening concrete and preparation method thereof

    CN121377687A